The Age-Friendly Community Movement in Maine - Oh, Patrica (Maine Policy Review, 2015)
Patricia Oh describes how age-friendly communities can provide residents of all ages what they need and want from their communities. She presents the broad guidelines for the integrated community planning necessary to create environments that support optimal aging and gives examples from places in Maine that are adopting the age-friendly community approach.